2015
DOI: 10.1093/pcp/pcv063
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the NADPH Oxidase RBOHD During Plant Immunity

Abstract: Pathogen recognition induces the production of reactive oxygen species (ROS) by NADPH oxidases in both plants and animals. ROS have direct antimicrobial properties, but also serve as signaling molecules to activate further immune outputs. However, ROS production has to be tightly controlled to avoid detrimental effects on host cells, but yet must be produced in the right amount, at the right place and at the right time upon pathogen perception. Plant NADPH oxidases belong to the respiratory burst oxidase homol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
386
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(430 citation statements)
references
References 102 publications
10
386
0
2
Order By: Relevance
“…Together, the results suggested Ca 2+ -independent phosphorylation of this site. Thus, the authors suggested that BIK1-mediated, Ca 2+ -independent phosphorylation occurred upstream of Ca 2+ and primed AtRBOHD for Ca 2+ regulation (Kadota et al, 2014(Kadota et al, , 2015. This model is also in agreement with the observation that in HEK cells Ca 2+ stimulation did not lead to RBOH activation in the presence of a kinase inhibitor (Kimura et al, 2012).…”
Section: Regulation Of Rbohs By Phosphorylation In Plantasupporting
confidence: 77%
See 1 more Smart Citation
“…Together, the results suggested Ca 2+ -independent phosphorylation of this site. Thus, the authors suggested that BIK1-mediated, Ca 2+ -independent phosphorylation occurred upstream of Ca 2+ and primed AtRBOHD for Ca 2+ regulation (Kadota et al, 2014(Kadota et al, , 2015. This model is also in agreement with the observation that in HEK cells Ca 2+ stimulation did not lead to RBOH activation in the presence of a kinase inhibitor (Kimura et al, 2012).…”
Section: Regulation Of Rbohs By Phosphorylation In Plantasupporting
confidence: 77%
“…FLAGELLIN-SENSITIVE2 (FLS2) and EF-TU RECEPTOR, which recognize flg22 and elf18, associate in a complex with the Leu-rich repeat receptor-like kinase (LRR-RLK) BRASSINOSTEROID INSENSITIVE1-ASSOCIATED RECEPTOR KINASE (BAK1) and receptor-like cytoplasmic kinases such as BOTRYTIS-INDUCED KINASE1 (BIK1; Fig. 1; for review, see Kadota et al, 2015).…”
Section: Regulation Of Rbohs By Phosphorylation In Plantamentioning
confidence: 99%
“…Recent reports also showed that the dynamics of AtRbohD are regulated by PM microdomains (Hao et al, 2014). At-RbohD has been shown to play an important role in innate immunity in Arabidopsis (Kadota et al, 2015) and belongs to same clade with Os-RbohB and Os-RbohH (Supplemental Figure 11A). Taken together with the data that OsRbohB contributes to resistance to rice blast fungus infection, simultaneous localization of Os-Rac1 and Os-RbohB/H to PM microdomains in response to chitin is likely to be necessary for the activation of Os-RbohB/H by activated Os-Rac1.…”
Section: Role Of Pm Microdomains In the Rac1-rbohb/h-mediated Mti Patmentioning
confidence: 89%
“…For example, FLS2-mediated flg22 perception and signaling requires transphosphorylation events that occur in the receptor complex (Macho et al, 2015). In addition, the transmembrane protein RBOHD, an NADPH oxidase responsible for the production of extracellular ROS, is activated through transphosphorylation by the receptor-like cytoplasmic kinase BIK1 and calcium-dependent protein kinases (Kadota et al, 2015). Mutation of the conserved Lys residue in the kinase domain of the Ser/Thr protein kinases is known to abolish kinase activity and thereby signaling Lin et al, 2015).…”
Section: Some Of the Largest Gene Families In Plants Encodementioning
confidence: 99%